2021
DOI: 10.3390/pharmaceutics13091413
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Poly(N-vinylpyrrolidone) Nanoparticles Conjugated with DR5-Specific Antitumor Cytokine DR5-B for Targeted Delivery to Cancer Cells

Abstract: Nanoparticles based on the biocompatible amphiphilic poly(N-vinylpyrrolidone) (Amph-PVP) derivatives are promising for drug delivery. Amph-PVPs self-aggregate in aqueous solutions with the formation of micellar nanoscaled structures. Amph-PVP nanoparticles are able to immobilize therapeutic molecules under mild conditions. As is well known, many efforts have been made to exploit the DR5-dependent apoptosis induction for cancer treatment. The aim of the study was to fabricate Amph-PVP-based nanoparticles covale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…To obtain fluorescently labeled protein DR5-B-iRGD, first the DR5-B-iRGD amino acid sequence was genetically modified at the N-end by replacing the amino acid residue valine in the 114 position to cysteine by site-directed mutagenesis. The cysteine-modified proteins DR5-B and DR5-B-iRGD were obtained by the method earlier reported for DR5-B [ 45 ]. Further, the cysteine-modified proteins DR5-B and DR5-B-iRGD were labeled by maleimide chemistry coupling with the fluorescent dye sulfo-Cyanine 3 maleimide (Lumiprobe, Moscow, Russia) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain fluorescently labeled protein DR5-B-iRGD, first the DR5-B-iRGD amino acid sequence was genetically modified at the N-end by replacing the amino acid residue valine in the 114 position to cysteine by site-directed mutagenesis. The cysteine-modified proteins DR5-B and DR5-B-iRGD were obtained by the method earlier reported for DR5-B [ 45 ]. Further, the cysteine-modified proteins DR5-B and DR5-B-iRGD were labeled by maleimide chemistry coupling with the fluorescent dye sulfo-Cyanine 3 maleimide (Lumiprobe, Moscow, Russia) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies [ 5 , 6 , 12 , 26 ], we determined the IMC loading efficiency, capacity, and stability of Amph-PVP derivatives with a different molecular weight of polymer hydrophilic fragment and length of anchor long-chain aliphatic hydrophobic fragment. Furthermore, we assessed the in vitro IMC release performance and the cytotoxicity of these nanoparticles [ 11 , 12 , 26 ]. The respective studies demonstrated the excellent biocompatibility and performance of PVP nanoparticles, duplicated in an in vivo acute toxicity determination model.…”
Section: Resultsmentioning
confidence: 99%
“…According to the method previously developed by our group, Amph-PVP polymer (PVP-OD4000) was synthesized by free-radical polymerization of N-vinylpyrrolidone monomer in the presence of azobisisobutyronitrile (AIBN) as initiator and mercaptoacetic acid (MAA) as chain-growth regulator. The following coupling reaction between carboxyl end-capped poly- N -vinylpyrrolidone with aliphatic n-octadecylamine (OD) in the presence of N, N’-dicyclohexylcarbodiimide (DCC) resulted in the desired polymer [ 24 , 25 , 26 ]. The resulting PVP-OD4000 amphiphilic polymer consists of a hydrophilic macromolecular fragment of PVP with 4000 Da molecular weight and one anchor hydrophobic n-alkyl octadecyl group.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained P-DR5-B nanoparticles enhanced the cytotoxicity of free DR5-B proteins in vitro in monolayer cell cultures and multicellular tumor spheroids of colon carcinomas HCT116 and HT29 and breast adenocarcinoma MCF-7 cells without cytotoxicity to normal cells. Taking into account the Amph-PVP ability to be loaded with a wide range of low-molecular-weight antitumor chemotherapeutics into hydrophobic core and the feasibility of conjugation with hydrophilic therapeutic molecules, it can be further developed into a versatile system for targeted drug delivery to tumor cells [ 98 ].…”
Section: Polymer-based Systems For Nanodelivery Of Trail Pathway-targ...mentioning
confidence: 99%